The contribution of technology in business growth: The case of Greek ladies - Angelina Vassilakopoulou (Journal of Innovation and Entrepreneurship, 2013)
The overall image of the use of digital technology by Greek women is not that encouraging. In information communication technology companies in the Greek market, there are only few ladies in high management mainly related to HR and marketing functions. The statistics on internet use show that although its penetration to the population is growing rapidly, there is a steady 10% gap between men (55%) and women (45%) use. It also becomes obvious, in relevant market surveys, that the internet is commercially underutilized in Greece, in comparison with the European average. Greece, in financial crisis, should leverage on technology in order to support financial development. However, there are few brilliant examples of Greek business ladies who have developed their businesses 'online'. Using digital media, social networks, applications, etc., they managed to break language and geographical barriers and set up their own micro-operations, responding to customer requests in the broader area or even globally. One could also find some interesting business examples from other European countries, from distant or dispersed areas. These micro-businesses cover multiple market industries even non-conventional ones such as e-tailing, publishing, energy consumption, specialized handcrafted goods. Here, we refer to hints and tips of the micro-business owners that led them to success over the internet and its potential impact on business growth. Moreover, since ladies in business usually have multiple roles to balance effectively in their lives, we will examine the impact of the systematic use of digital technology in work-life balance. In fact, the working population can save some time using digital technology to cover multiple needs. This may affect the working time zones, communication with family members, relationships to friends access to services, and the possibility to reserve some valuable 'quality time' for the lady entrepreneur. Having that available, women entrepreneurs can choose how to invest in time again: back in business, share it with family, and keep it valuable for herself so they can look at IT as their ultimate ally for business and personal development.
Keywords: 650; stereotypes; new media; time management; diversity; technology; tips; internet; business